Experimental Investigation of Torque Transmitting Ability of Innovative Movable-teeth CVT - Feng Nenglian; Mi Lei (Jixie chuandong)
In order to investigate the torque transmitting ability of the innovative Movable- teeth CVT（ i MCVT）,its construction and principle are analyzed,and then,a comparative analysis with the torque transmitting ability of the metal belt continuously variable transmission which is based on friction transmission is carried out. Lastly,the transmission efficiency test platform is set up to investigate the relationship between the transmission efficiency and the transmission torque of the i MCVT under three conditions. The results show that when the i MCVT operating stable under three conditions, the transmission torque could reach to about 220 N·m. When the transmission torque is at 180 220 N·m,the i MCVT transfer stably and the transmission efficiency is high. Compared with the metal belt continuously variable transmission,the torque transmitting ability of i MCVT is stronger,and still could keep the high transmission efficiency of 92% when transferring the high torque.